Stability and electronic structures of isoelectronic impurity complexes in Si: First-principles study. (5th September 2016) - Iizuka, Shota; Nakayama, Takashi
Abstract: The stability and electronic structures of various isoelectronic cation+anion pairs in Si were studied by first-principles calculations. It was shown that the nearest-neighboring substitutional configuration is the most stable structure for most cation+anion pairs, while B+N, Mg+O, and Be+O pairs preferentially occupy a single Si site owing to the small atomic radii of B, N, and O atoms. We found that only Al+N, Ga+N, and In+N pairs produce electron-unoccupied weakly localized states in the band gap of Si, reflecting the large negativity of N atoms. We also showed that single N doping produces N+N pairs and that such pairs induce no electronic states in the band gap of Si. Therefore, the codoping of Al and N atoms is essential to produce an electronic state in the Si band gap and increase the tunneling current in Si tunneling field-effect transistors.